STRATEGI PEMILIHAN KONTRAKTOR PERANGKAT LUNAK DENGAN MEMANFAATKAN PENGETAHUAN TERHADAP CAPABILITY MATURITY MODEL INTEGRATION FOR DEVELOPMENT (CMMI FOR DEV) - Bayu Adhi Tama; Indra Silanegara (Jurnal Sistem Informasi, 2009)
Given out a same software development to different contractors will produce a certain different software result. This principle can be used by project manager in selecting software contractors. Therefore, a strategy in choosing the best candidate is needed. To support this activity, CMMI for Dev can be used as guidance or reference for its reader, especially for project managers and their teams about how to assess quality and productivity of activity process in a software company. This knowledge can be applied in selecting the candidate in order to work together for developing the required software. Also, the process area of CMMI for Dev promotes strategy in selecting the candidate thatwill develop the software in an agreement. However, due to the limitation the writer have, not all aspect can be discover and worth for further research in the future. Kata kunci : Kontraktor perangkat lunak, strategi-strategi, Capability Maturity ModelIntegration for Development (CMMI for Dev), Process Area (PA).